Tinjauan Fatwa DSN MUI Nomor 19/DSN MUI/IV/2001 terhadap Implementasi Pembiayaan Dana Qarḍ di Lembaga Amil Zakat Masjid Raya Bintaro Jaya MRBJ - Maulidah Nur Afifa; Inayah Hanoum; Dewi Lestari (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
The background of this research is based on the importance of Sharia-based social financing in assisting people in need without involving elements of riba, while ensuring that its practices remain aligned with Islamic economic law principles. This study aims to analyze the implementation of qard financing at the Masjid Raya Bintaro Jaya Amil Zakat Institution (MRBJ) and to examine its compliance with the provisions set by the Dewan Syariah Nasional Majelis Ulama Indonesia, through Fatwa Number 19/DSN-MUI/IV/2001 concerning Al-Qard. This research employs a qualitative method with a case study approach. Data collection techniques include interviews, observations, and documentation. The research subjects consist of zakat institution administrators and beneficiaries. (mustahiq) of the Qard Financing Program. The results indicate that the implementation of Qard financing at MRBJ has been carried out as a form of community economic empowerment, with a relatively simple distribution mechanism oriented toward the needs of the mustahiq. However, in practice, there are still several aspects that have not been optimal, particularly in terms of assistance and monitoring for the beneficiaries. Therefore, this study concludes that although qard financing at MRBJ. provides significant social benefits, there is a need to enhance Sharia understanding and improving institutional governance to ensure optimal implementation in accordance with the principles established by the DSN-MUI fatwa with the principles established by the DSN-MUI fatwa.